Gambaran Tekanan Intraokuler Terhadap Risiko Glaukoma Pada Berbagai Derajat Miopia di Rumah Sakit Mata Makassar Tahun 2025 - Yuni Lawati; Purnamanita Syawal; Nursapriani (RS Mata Makassar: Journal of Ophthalmology, 2025)
This study aimed to describe intraocular pressure (IOP) and the risk of glaucoma at various degrees of myopia in patients at the Makassar Eye Hospital in 2024. A descriptive analytical observational method with a cross-sectional approach was used. A total of 166 eyes from myopic patients met the inclusion criteria. Data were analyzed using the Chi-square test to evaluate the relationship between IOP and myopia degree. Results showed that IOP tended to increase with age, with higher values observed in females and in patients with higher degrees of myopia. The statistical test revealed a significant correlation (p = 0.04) between IOP and the degree of myopia. In conclusion, the higher the degree of myopia, the greater the risk of increased intraocular pressure and potential glaucoma development.